1989
DOI: 10.1103/physrevb.40.11965
|View full text |Cite
|
Sign up to set email alerts
|

Scanning tunneling microscopy of the charge-density wave in orthorhombicTaS3

Abstract: The Rapid Communications section is intended for the accelerated publication of important new results. pince manuscripts submttted to this section are gt en priortty t~~~tm~~t both in the~dit~~ial their submittal letter why the workj ustlftes this special handling A . Rapid Communication should be no longer than 3s/~printed ages and must be accompanied by an abstract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…they are not localized on any particular chains) [26]. It is very probable that the origin of the preferred position of the REHAC elementary excitation are the CDW dynamical defects, as sudden sliding of CDW for one lattice spacing in the chain direction has been observed even at room T [26]. In this very delicate entanglement of the lattice and CDW(s), it might be that the lattice tries to stagger the chains in order to reduce the Coulomb repulsion.…”
mentioning
confidence: 99%
“…they are not localized on any particular chains) [26]. It is very probable that the origin of the preferred position of the REHAC elementary excitation are the CDW dynamical defects, as sudden sliding of CDW for one lattice spacing in the chain direction has been observed even at room T [26]. In this very delicate entanglement of the lattice and CDW(s), it might be that the lattice tries to stagger the chains in order to reduce the Coulomb repulsion.…”
mentioning
confidence: 99%
“…The CDW of TaS 3 has been analyzed using various methods at a temperature below T p , including X-ray diffraction, electron diffraction, and scanning tunneling microscopy. The low-temperature characterization of CDW reports the existence of incommensurate and commensurate CDW depending on the temperature range [ 22 , 23 , 24 , 25 ]. Between T p and 100K, an incommensurate CDW with the wave vector of is observed.…”
Section: Resultsmentioning
confidence: 99%
“…However, when the temperature surpasses the transition temperature, the periodicity of CDW becomes weak. For instance, from an STM study conducted at room temperature, a weak sign of CDW was observed [ 25 ]. Furthermore, above T p , the possibility of forming a pseudogap was proposed.…”
Section: Resultsmentioning
confidence: 99%
“…The surfaces of many CDW systems have been studied especially by STM. The CDW phase is present at the top layer and can display a perfect long range order over hundreds of nanometers, like in the quasi-1D Rb 0.3 MoO 3 [34], K 0.9 Mo 6 O 17 [35], TaS 3 [36], NbSe 3 [37,38,39] and in the quasi-2D TbTe 3 [40,41] and 1T-TaS 2 [42]. Moreover, several groups observed a surface CDW using grazing incident X-ray diffraction in NbSe 2 [43] and K 0.3 MoO 3 [44].…”
Section: Discussionmentioning
confidence: 99%
“…As proposed by Yetman and Gill [18] and in [47], this effect could be associated to a commensurate CDW pinned to the crystal lattice at the surface in contrast to an incommensurate CDW in the bulk. Gammie et al measured the surface CDW modulation in TaS 3 to be approximately at the commensurate value 4c 0 × 10b 0 [48] where c 0 and b 0 are the crystal lattice parameters. Brun et al measured by STM the CDW wavevector in Rb 0.3 MoO 3 at the commensurate value q cdw = ±0.25b * + (a + 2c) * [49].…”
Section: Discussionmentioning
confidence: 99%